PENCITRAAN TANAH TORAJA DALAM PERSPEKTIF WISATA BUDAYA (Studi Kasus Pelestarian Budaya Melalui Transformasi Suku Tanah Toraja) - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Human development and cultural progress rapidly , which in the beginning of human life ranging from farmingto those who live on land or mountains , then the other life of fishermen that are not menetap. Both made the life oftime to time often move from one place the new elsewhere and may provide a better income than the sebelumnya.Proses a simple process to maintain the necessities of life .Man is as a result of the displacement of an increasingly uncertain start to think to stay longer and even berpindah.Dari is where people begin to believe that life is not just related to the natural course but no more shouldthey believe that confidence in the authorities and human nature ( Supreme Creator ) . they perform rituals asa token of gratitude , such as discard at sea off the coast of crops / with the procedures / persembahannya.Dariwhere they make symbol - symbol , for example, in ceremonies of birth, death , marriage , election of indigenousleader in terms of governance and munculah budaya.sosial and identity ( a state that has a unique characteristicor characteristics of the individual to identify where someone or something seen ) is typical of the houses, thedress code , everything is part of asimulasi of local culture in the archipelago as well as any which is the cultureof Toraja Land .